2018
DOI: 10.1186/s12909-018-1121-6
|View full text |Cite
|
Sign up to set email alerts
|

Training programmes to improve evidence uptake and utilisation by physiotherapists: a systematic scoping review

Abstract: BackgroundResearch training programmes are a knowledge translation (KT) intervention which aim to improve research evidence uptake by clinicians. Whilst KT training programmes have been reported to significantly improve evidence uptake by physiotherapists, it is unclear which aspects of training optimally assist KT into physiotherapy practice. The purpose of the review was to establish the body of evidence regarding KT training programmes to improve physiotherapists’ use of evidence-based practice (EBP) and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 57 publications
0
60
0
1
Order By: Relevance
“…As expected, experience in EBP training was related to higher scores in the Quick‐EBP‐VIK scale. Some researches supported the effectiveness of comprehensive and multiple‐component training programs for health professionals (Häggman‐Laitila, Mattila, & Melender, ; Stander, Grimmer, & Brink, ). Meanwhile, research suggested that face‐to‐face training can significantly improve health care professionals’ EBP knowledge, attitudes and implementation than self‐directed training programs (Fei et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, experience in EBP training was related to higher scores in the Quick‐EBP‐VIK scale. Some researches supported the effectiveness of comprehensive and multiple‐component training programs for health professionals (Häggman‐Laitila, Mattila, & Melender, ; Stander, Grimmer, & Brink, ). Meanwhile, research suggested that face‐to‐face training can significantly improve health care professionals’ EBP knowledge, attitudes and implementation than self‐directed training programs (Fei et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, efforts were made to support health care professionals with evidence uptake . Knowledge translation (KT) strategies, specifically evidence‐based practice (EBP) training programmes, have been developed to improve evidence‐uptake behaviours to increase health care professionals' CPG use in practice . However, there may be different barriers and facilitators to CPG use for different health care providers, in different settings, and there is no one‐size‐fits‐all approach to identifying or addressing them .…”
Section: Introductionmentioning
confidence: 99%
“…However, there may be different barriers and facilitators to CPG use for different health care providers, in different settings, and there is no one‐size‐fits‐all approach to identifying or addressing them . In the health care sector, KT strategies, informed by facilitators and barriers to its local implementation, have a better chance of being successful …”
Section: Introductionmentioning
confidence: 99%
“…Taking a page from qualitative research, we encourage authors to include a brief reflexivity section in which they report and reflect on the characteristics of their team in relation to the study's design, data collection and analysis, and reporting. 36 This information increases transparency and allows readers to make informed judgments about the conduct of the review, as well as its findings and interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen reviews (12.9%) cited following the PRISMA, 31 and five (5.0%) the PRISMA-ScR. 13,[32][33][34][35][36] Table 3 summarizes the components of the PRISMA-ScR present in the included scoping reviews. For details by study, see https://doi.org/10.6084/m9.figshare.12699698.v1.…”
Section: Figure 1: Flow Diagram Of Study Inclusion Processmentioning
confidence: 99%